Testing disease resistance in autumn wheat genotypes by means of field experiments - Pepó, Péter (Acta Agraria Debreceniensis, 2001)
According to our scientific results we can state that we have to use integrated pesticides management in crop protection against the diseases of winter wheat. One of the most important elements of IPM is to select a genotype characterised by good resistance to diseases (and by high yield ability and excellent baking quality). It is especially important that the wheat variety have tolerance against not only to one or two leaf and spike (grain) diseases, but „complex” tolerance. It is not necessary to give up the growing of a variety which has susceptibility to different diseases because we can protect it using appropriate chemical management. In the intensive growing stage of wheat (BBCH 32-37) we can use a noncompulsary fungicide-treatment (depending on e. g. the infection, ecological conditions) and, at the beginning of the flowering stage (BBCH 59-65), we have to use a compulsary fungicide-treatment (in spite of e. g. special weather conditions, resistance genotype)to ensure high yield and good quality.